Perceptions and understanding of Attention Deficit Hyperactivity Disorder amongst Foundation Phase teachers at independent schools in Johannesburg - Jaye, Tamara (My University, 2020)
Attention Deficit Hyperactivity Disorder (ADHD) is a common neurodevelopmental condition comprising hyperactivity, inattention, and impulsivity. It is pervasive across various settings and leads to functional impairment, with the diagnosis of this condition increasing significantly over the past two decades. The classroom is a difficult environment for the child with ADHD as the symptoms of the condition hinder behaviour that is required in a school setting. Teachers play a crucial role in this condition, being expected to notice the signs of ADHD, be a collateral in the diagnosis, manage the child’s behaviour in class, and administer medication. This study was to determine Independent School Foundation Phase teachers’ knowledge and perceptions of the symptoms, associated features and treatment of children diagnosed with ADHD. A quantitative approach with a cross-sectional research design was used to conduct the study. A demographic survey, followed by a self- administered questionnaire called the Knowledge of Attention-Deficit Disorder Scale (KADDS) was utilised for a sample of 95 teachers at 9 independent schools in Johannesburg. In addition, a focus group was conducted with several candidates using open-ended questions. The results showed that this group of teachers attained the highest score compared to other research bodies where the KADDS was utilized. The majority of Independent teachers are knowledgeable about the symptoms of ADHD, less so about ADHD treatment, and features of ADHD are poorly understood. Experience with children with ADHD in their classroom correlated with more ADHD knowledge. Workshop attendance and reading material on ADHD were shown to improve knowledge and perceptions about ADHD amongst teachers
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Medicine in Child Health (Neurodevelopment)